Application of Ziziphus Jujube (Red Date), Camellia Sinensis (Black Tea) and Aleurites Moluccana (Candle Nut) Marinades as Beef Meat Tenderizer - Afifi Ismail, Mohamad; Anuar Ibrahim, Mohamad; Rashedi Ismail-Fitry, Mohamad (International Journal of Engineering and Technology, 2019)
This study was carried out to analyse Ziziphus jujube (red date), Camellia sinensis (black tea) and Aleurites moluccana (candlenut) extract as the potential beef tenderizer. The beef meat chunks (3cm3) were marinated with the extracts at different concentrations (20%, 40% and 60%) for 24 hours at 4ºC. Both raw and cooked samples were subjected to physicochemical analyses and sensory evaluation. Overall, there were slight changes in pH values and increased in moisture content for all the treated samples. The increased concentration of extracts resulted in decreased cooking loss and the hardness from texture profile analysis (TPA) of the treated sample compared to the control. The colour analysis showed a significant (p<0.05) different in term of lightness, redness and yellowness of all treated meat chunks. Increased concentration of extracts reduced the redness of meat samples. The sensory evaluation indicated that the tenderness, juiciness and overall acceptability of all treated samples were significantly (p<0.05) higher compared to control. It can be suggested that the marination of meat with Ziziphus jujube (red date), Camellia sinensis (black tea) and Aleurites moluccana (candlenut) extracts have the ability to tenderize the meat as the toughness decreased in all treated samples with Ziziphus jujube (red date) was the best tenderizer.